Influences Of Green Building Technology(Gbt) Adoption On Community Resilience In The Context Of Covid-19 Pandemic - Bahtar@Mokthar, Siti Musliha (Universiti Sains Malaysia, 2021)
Green Building Technology (GBT), which is also known as Green Construction, is the implementation of environmentally responsible and resource-efficient design throughout the life cycle of a structure, building, or commercial space. Green buildings protect valuable natural resources while improving our quality of life. The Covid-19 epidemic is bringing about changes and we may adjust the way we construct our living environments to handle the pandemic. A healthy and comfortable living environment is necessary for mental and physical well-being. Green Building Technology (GBT) adoption gives many influences towards its occupants based on the aspect of sustainability in relation to the pandemic of Covid-19. However, the construction industry in our country is still lacking in terms of the characteristics of green building to face the challenges of Covid-19 pandemic. Covid-19 has led to a new perspective in contemporary residential building design, indicating that living circumstances should be reconsidered and upgraded for better resilience towards this pandemic. This research aims to determine the influences of Green Building Technology (GBT) adoption on community resilience in the context of Covid-19 pandemic from the perspective of sustainability. The results from the survey shows that sustainability elements of environmental aspects had the most significant influence on the adoption of GBT. It is expected that this research provide inputs and ideas to the construction stakeholders in realizing that GBT adoption provides various benefits towards community resilience while combating Covid-19 pandemic besides can be used as future references for comparative studies.